The Relationship Between Successful Intelligence and Its Practice in Education Among Private School Teachers in Amman - Alzoubi, Ahmad (Jordan Journal of Educational Sciences, 2017)
This study aimed at investigating the relationship betweenself assessment of successful intelligence (ASI) with it spractice in teaching for successful intelligence (TSI) among private school teachers in Amman. The sample included 221 teachers in the humanities and scientific disciplines. The researcher applied successful intelligence inventory, and the practice ofteaching for successful intelligence scale. Results indicated that the level of ASI was high, whereas the level of TSI was moderate. The study showed significant positive correlations between ASI with TSI. Also, results of regression analysis revealed that the ASI predicted of TSI (R square=,56). No significant differences were found in ASI due to gender or academic specialization. The study found significant differences in TSI due to academic specialization. Whereas there were no significant differences in ESI due to gender. Finally, the study recommended the necessity to train teachers on the application of successful intelligence in education, especially creative intelligence